A Critical Evaluation of WOORDEBOEK/WÖRTERBUCH with Regard to Source- and Target-Language Forms - Pienaar, Sole (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Afrikaans and Dutch))—University of Stellenbosch, 2006.